PENYULUHAN MENGENAI KONSEP ZERO WASTE DAN PENTINGNYA PENGELOLAAN SAMPAH MANDIRI BAGI MASYARAKAT DI KOMPLEKS MABAD 65 REMPOA CIPUTAT TANGERANG SELATAN - Miranti Mayangsari; Nurhayati Nurhayati; Junaenah Junaenah; Nia Kurniasih (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
An increasing number of populations, lifestyle changes and an increase in consumerism escalated the total amount of waste generated. It was estimated that 85,000 tons of waste were produced daily in Indonesia in which 40% were domestic waste. Waste generated in urban areas had generally been finished in the landfill without being processed before. This condition has raised various problems at landfills in Indonesia.The Mabad 65 complex is located in Rempoa, Ciputat, South Tangerang. South Tangerang City is one of the buffer zones of the Capital of Jakarta which has developed into a high-density residential area. At this time, the domestic waste generated by all residents of Mabad 65 is transported by garbage officers to be moved at the TPS before finally being transported to the landfill without being sorted and processed before. The majority of residents have not made efforts to reduce their waste generation.Based on the existing condition in the Mabad 65 Complex, it is felt necessary to educate residents about the zero-waste lifestyle. The method used in the community service was counseling. The participants were Mabad 65's residents and RT RW administrators in the Mabad 65 Rempoa complex. The counseling program was carried out on Monday, December 9, 2019.The results of this community service activity were the residents as well as the RT RW administrators became more concerned about the problem of waste in Indonesia, especially about the landfill capacity and the importance of reducing and processing waste at the domestic waste source of waste. Residents also understand how to minimize household waste generation by using the 3-AH method, which is to prevent, to sort and to process. Moreover, residents were also enthusiastic about the source scale waste management program that brought economic opportunities. The trouble faced by the RT RW administrators was the governance system of the waste bank program.Keywords: zero waste lifestyle, do mestic waste, solid waste treatment